Smart Building Perspective in support Energy Security - Doddy Setiawan; Yanif Dwi Kuntjoro (The Republic of Indonesia Defense University, 2015)
The utilization of solar energy in the Auditorium Indonesian Defense University (IDU) is not optimal because problem on the system off-grid The problems that occur due to technical factors (operating system is not in accordance with the concept of smart building) and non-technical (HR, Budget Maintenance, and SOP / SOM). The method used by the researchers is the optimization of observation and interviews. Optimization of solar energy utilization in Building IDU Auditorium is affected by three factors such as human resources, maintenance budgets, and standards of procedure (SOP) and the standard of maintenance (SOM). Besides the three factors were the use operational system that refers to the concept of smart building to be responsible for optimizing the utilization of solar power to support energy security